Future-oriented thinking promotes positive attitudes toward the “Help Mark” in Japan - Hashimoto, Hirofumi; Maeda, Kaede; Sato, Kosuke (Frontiers in Rehabilitation Sciences, 2022)
The “Help Mark,” created in Japan, is worn by people who need help in public settings. It is designed to induce help from others for those in need of help because of their hidden disabilities or health conditions. Several attempts have been made to publicize the meaning and implications of this wearable sign through various media. However, it is difficult to assert whether there is sufficient awareness regarding this sign in Japanese society. The purpose of this study was to examine the type of messages that are more effective in promoting the “Help Mark” system (Study 1). Additionally, based on the data obtained in Study 1, we presented a newly designed poster to promote the “Help mark” sign and attempted to empirically examine the effect of this poster (Study 2). The results suggest that a message that reflects that the “Help Mark” is for “everyone,” based on future-oriented thinking, is more effective. Furthermore, it was indicated that people who saw the poster containing a message implying that the “Help Mark” is “for everyone” reported increased positive attitudes toward the “Help Mark” system. These results indicate that encouraging future-oriented thinking may lead to positive attitudes regarding the “Help Mark” system.